Vehicle Collision Detection and Emergency Contact - V P, Dhivya; M, Anisha; V M, Ashaleshwaran (2024 2nd International Conference on Artificial Intelligence and Machine Learning Applications Theme: Healthcare and Internet of Things (AIMLA), 2024)
One of the primary causes of auto accidents is speed. Numerous lives may have been saved if rescue workers had been able to get accident information and get there in time. The accident detection systems that are the subject of this research utilize many components in order to detect accidents and alert rescue personnel when help is needed. An efficient automated accident detection system that instantly alerts emergency services to the accident's location is crucial for protecting people's precious lives. The recommended approach deals with accident identification and notification. After reading it, it sends the afflicted vehicle's exact latitude and longitude to the emergency response provider closest to you. The project's objective is to find incidents and notify the rescue squad as soon as feasible.